Does Performance Budgeting Work? : An Analytical Review of the Empirical Literature - Robinson, Marc (IMF Working Papers; Working Paper ;, 2005)
This paper attempts to ascertain what light the empirical literature sheds on the efficacy of performance budgeting. Performance budgeting refers to procedures or mechanisms intended to strengthen links between the funds provided to public sector entities and their outcomes and/or outputs through the use of formal performance information in resource allocation decision making. The paper seeks to identify and examine the literature on "governmentwide" performance budgeting systems-that is, systems used by central budget decision makers (ministry of finance and political executive) to link the funding they provide to those agencies' performance. Performance budgeting principles are, however, applied not only on a government wide basis, but also in funding systems applied to specific categories of government services. This paper does not attempt to review the empirical literature on all such "sectoral" performance budgeting systems. Rather, it undertakes a case study of the literature on one specific sectoral system-output-based hospital funding systems.